ENTERPRISE MANAGEMENT IN THE CONDITIONS OF DIGITALIZATION OF THE ECONOMY - MYKOLIUK, OKSANA; BOBROVNYK, VALENTYNA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article investigates the role of digital transformation processes and their impact on enterprise management. It is emphasized that the introduction of innovative technologies in the enterprise will open new opportunities for further effective development and implementation of positive changes. The need to optimize management processes in the enterprise by adapting them to the conditions of digitalization, which requires the use of qualitatively new approaches to digital transformation of economic entities. The essence and meaning of the term "digitalization" is revealed, the main goals and directions of digital development are defined. The importance of digitalization of the economy as an innovative dynamic process, which is based on the active introduction of innovations and information and communication technologies in the economic activity of enterprises, is substantiated. The main components of the digital economy (support infrastructure, e-business, e-commerce) are identified and their impact on innovative business development is studied. The classification of enterprises according to the level of digitalization is carried out and the necessity of their orientation in the direction of introduction of cyberphysical systems, the Internet of Things, big data, 3D-modeling and 3D-graphics into their own activity is substantiated. The state of digital transformation at domestic enterprises is analyzed, the ratio of the use of digital technologies in business activity is revealed. The main problems faced by enterprises on the way to the introduction of innovative technologies are identified. The presence of the necessary conditions for the implementation of the domestic digital breakthrough and technological transition of enterprises to a higher level has been determined. It is concluded that the digitalization of business is a condition for improving its competitive position in the market and the driving force of the country’s economy and its investment attractiveness.